2020
DOI: 10.1253/circrep.cr-20-0111
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Significance of Post-Procedural Left Ventricular Ejection Fraction Following Atrial Fibrillation Ablation in Patients With Systolic Dysfunction

Abstract: Study Population This retrospective observational study screened 1,077 consecutive patients undergoing radiofrequency catheter ablation for AF (Figure 1). Of patients undergoing circumferential pulmonary vein isolation (PVI) between August 2009 and May 2019, 195 who had impaired LVEF (<50%) were enrolled in the present study. Patients who underwent cardiac resynchronized therapy after the procedure, those who were followed up for <6 months after the procedure, and those who did not receive echocardiographic ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
13
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 23 publications
(14 reference statements)
1
13
1
Order By: Relevance
“…2 In the study of Yazaki et al, some patients underwent multiple catheter ablations to treat recurrent atrial tachyarrhythmia. 3 The next concern is whether such interventions could also ameliorate cardiac function, as well as clinical outcomes, following recovery to sinus rhythm.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…2 In the study of Yazaki et al, some patients underwent multiple catheter ablations to treat recurrent atrial tachyarrhythmia. 3 The next concern is whether such interventions could also ameliorate cardiac function, as well as clinical outcomes, following recovery to sinus rhythm.…”
mentioning
confidence: 99%
“…2 Yazaki et al demonstrated that an incremental improvement in left ventricular ejection fraction (LVEF) following catheter ablation for AF was associated with a greater clinical outcome compared with persistently impaired cardiac function. 3 Yazaki et al stratified clinical outcomes by post-procedural LVEF status. 3 Post-procedural clinical outcomes stratified by improvement in cardiac function vs. remaining cardiac function would be of great interest.…”
mentioning
confidence: 99%
See 3 more Smart Citations